CHALLENGES FACING SCHOOL STUDENTS IN QUR’AN MEMORIZATION: A QUALITATIVE STUDY - Nik Abdullah, Nik Md. Saiful Azizi; Mohd Sabbri, Fathiyah Solehah; Muhammad Isa, Rabi'atul Athirah (UNISZA, 2018)
This article explores the challenges faced by students in Qur’an memorization in the Taḥfīẓ class setting. A qualitative study through semi-structured In-depth interviews through one-on-one interactions were used to investigate participants’ views about their challenges on memorizing the Qur’an. The researchers used open-ended interview structure which included specific questions, followed up by probing questions to investigate the phenomenon in details. Participants in this study were made up of 6 Taḥfīẓ students (3 females and 3 males), whose ages ranged between 15 to 17-year olds, Findings from the study suggests that time constraint, lack of motivation, inability to recall, emotional challenges and external noise were among the problems that students faced in their journey to memorizing the Qur’an. The researcher also found that the students had less attachment to the Qur’an which make it difficult for them to memorize the Qur’an. Implications from this study raises awareness among teachers, students and parents and guardians who have send their children to Taḥfīẓ schools to memorize the Qur’an. In addition to this, the students themselves and teachers also were the source of motivation to memorize. By knowing the challenges in memorizing, this study can serve as reference in narrowing the gap on motivation in Qur’anic memorization. Hence, the researchers believe that this study will be much help for others to continue and elaborate more on the field of Qur’anic memorization in relation to motivation